The Renaissance Dam crisis and its impact on Egyptian-Ethiopian relations - Khalifa, Azar Abd (Al-Adab Journal, 2021)
Formerly known as the Millennium Dam and sometimes referred to as Hadassah, it is a gravitational dam under construction on the Blue Nile about 40 km east of Sudan in the Benishangul-Gumuz region, Ethiopia. With a capacity of 6,000 MW, the dam will become the largest hydroelectric power station in Africa at Its completion, and ranked 13th or 14th in the world, with the Krasnoyarsk Dam. The dam's reservoir will have a capacity of 63 billion cubic meters, making it one of the largest on the African continent.The main purpose of constructing the dam is to generate electric power, and the water will be returned to its downstream countries (Sudan and Egypt) after electricity generation and that this water is not consumed or used for irrigation.